P.S. 1 : Italian Studio Program 2000-2002. - Daolio, Roberto; Dini, Lamberto; Galasso, Alessandra; di Gropello, Giulio; Illy, Andrea; Pagano di Melito, Andrea; Di Pietrantonio, Giacinto; Tolomeo, Maria Grazia; Zannier, Sabrina; P.S. 1 Italian Bureau, Roma (Milano : Edizioni Charta, 2001)
Young Italian artists are exposed to the careful scrutiny of one of the most important international art institutions the P.S. 1 Contemporary Art Center of New York in association with the Museum of Modern Art. Since 1976, P.S.1 - MoMA has hosted the annual International Studio Program, in which eighteen artists are selected from around the world. This volume records the work of fifteen finalists of the 2000-2001 and 2001-2002 editions of the Italian grant competition. Chosen from 425 emerging Italian artists, their work perfectly represents the current panorama of Italian art. As always, it was the Italian Studio Program that promoted and coordinated the competition. For the fourth consecutive year, a young italian artist was given the opportunity to live and work in New York for a year. A committee chaired by Luigi Ontani was in charge of selecting the finalists. The winners were chosen by art independent jury formed by P.S. 1-MoMA.
Andrini, Alessandra ; Bertocchi, Davide ; Caravaggio, Gianni ; Galegati, Stefania ; Jeane, Norma ; Losi, Claudia ; Maggio, Elisabetta di ; Mala.Arti Visive ; Mocellin, Ottonella ; Nicoletta, Sandrine ; Piccioni, Roberta ; Puppi, Daniele ; Rivola, Fabrizio ; Xhafa, Sislej ; Zuffi, Italo
biog., ind. tent., gr. tent. p. 117-125
Italiaans & Engels
Italian Studio Program 2000-2002, Palazzo delle Esposizioni Spazio S8ZERO, Roma ; P.S.1 Contemporary Art Center, Long Island, 26.04.2001 - 11.06.2001
boek
Keywords: Italië